2002
DOI: 10.1103/physrevb.66.195410
|View full text |Cite
|
Sign up to set email alerts
|

Quantum electronic stability and spectroscopy of ultrathin Pb films onSi(111)7×7

Abstract: The growth of Pb on Si(111)7ϫ7 has been studied with photoelectron spectroscopy. At low temperature ͑110 K͒, Pb grows in a quasi layer-by-layer mode that allows for the direct observation of discrete quantum well states. The quantum well states are analyzed in terms of the Bohr-Sommerfeld phase quantization model using a phenomenological phaseshift function and reduced quantum numbers. Fermi-level crossings occur when the film thickness Ndϭn(F /2), where d is the atomic layer spacing and F the bulk Fermi wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…In this case, the thickness-dependent adsorption behavior is much more obvious. All CoPc molecules diffuse long enough and are able to reach the energetically favorable regions (10,12,14,17 and 19 ML) where stronger oxygen adsorption and oxidation are always observed to form an ordered self-assembled monolayer, leaving other regions (11,13,15,16, and 18 ML) intact. With this experiment, the influence thickness-dependent diffusion can safely be ruled out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the thickness-dependent adsorption behavior is much more obvious. All CoPc molecules diffuse long enough and are able to reach the energetically favorable regions (10,12,14,17 and 19 ML) where stronger oxygen adsorption and oxidation are always observed to form an ordered self-assembled monolayer, leaving other regions (11,13,15,16, and 18 ML) intact. With this experiment, the influence thickness-dependent diffusion can safely be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…For Pb, F ϭ 1.06 nm, which is nearly 4 times of the interplanar distance d 0 along the crystallographic [111] direction. This coincidence ( F Ϸ 4d 0 ) suggests that, when 1 ML of Pb is added or removed, electron interference will change from being constructive to destructive and vice versa, leading to a 2-ML modulation of the electronic structure (15)(16)(17)(18)(19). More accurate analysis indicates that the exact period should be 1.8 ML.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the quantum oscillations in superconducting transition temperature T c were observed, which correlate perfectly with the confined electronic structure. 36) Other novel properties induced by QWS, such as double-layer growth, [29][30][31]38) selective strip-flow growth and growth rate modulation, 39) oscillating perpendicular upper critical field, 40) thermal expansion, 41) adhesion force, 42) local work function (LWF), 43) and surface diffusion barrier, 44) have also been observed. In this article, we would mainly summarize these recent results on Pb/Si(111) by our group.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups observed that the stability of Pb islands depends on the thickness, magic and preferential heights of the islands were identified by their STM/STS measurements. 27) In the case of flat Pb films, ARPES studies revealed the significance of QSE on DOS(E F ) 31) and thermal stability of the Pb films, 11,32) and the stability was explained in terms of the electronic structure modulation by QWS. Quantum beating patterns in the thickness-dependent surface energy 32,33) were also observed, which, according to the simple picture mentioned above, should be a manifestation of the slight deviation from the perfect matching F ¼ 4a 0 .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these observations are the strong dependence of the Schottky barrier on the exact atomic structure 6 , the formation of magic height islands 7 , anomalies in the superconductivity transition temperature [8][9][10] , oscillations of the work function and extremely long excited state life times 11,12 , and the observation of a Rashba-type spin splitting 13 . The origin of many of these phenomena lies in the peculiar electronic structure of Pb on Si(111) manifested in the high in-plane effective mass [14][15][16] . A control of this effective mass can thus also give control over many of the other physical properties which make Pb films on Si such a rich research subject.…”
Section: Introductionmentioning
confidence: 99%